Recent advances in adoptive cell therapy for cancer immunotherapy - Qian, Jiameng; Liu, Yuhua (Frontiers in Immunology, 2025)
Adoptive cell therapy (ACT), a key direction in tumor immunotherapy, has achieved remarkable progress in recent years. This paper systematically reviews the current status and future trends of ACT, covering lymphokine-activated killer cells (LAK), tumor-infiltrating lymphocytes (TIL), cytokine-induced killer cells (CIK), dendritic cells (DC), T cell receptor-modified T cells (TCR-T), chimeric antigen receptor T cells (CAR-T), natural killer (NK) cells, chimeric antigen receptor-modified NK cells (CAR-NK), and the emerging CAR-M. The paper focuses on emerging technological approaches, including universal CAR structural optimization, iPSC-derived cell products, multifunctional CAR design, and AI-assisted antigen screening. It also compares differences among various cell therapies in antigen specificity, efficacy persistence, safety, and clinical application challenges. The core contribution of this paper lies in synthesizing recent research advances to propose strategies for addressing tumor heterogeneity, antigen escape, cell persistence, and therapeutic safety in ACT. This provides a reference for future personalized and precision cell therapy approaches.